Post burn care: a psychological sequelae - Sulaiman, Wan Azman Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
Introduction: Burn injury is among the most common trauma cases admitted to hospital around the world. Burn treatment has underwent multiple level of paradigm shift from merely to get the burn victim survive to survive with reasonable quality of life in term of physical restoration for function and aesthetic value. Recent advancement in the management of post burn scar give more hope for burn victim to return to pre-burn physical function and aesthetic but burn injury does not only change a person physically, but invariably causes mental distress or psychological impairment especially in major burn cases. Study Objective: The objectives of this study is determine the effect of total body surface area (TBSA) of burns towards Posttraumatic stress disorders (PTSD), depression and quality of life (QOL) in major burn cases Methods: Majors burn patients who were treated in Hospital Universiti Sains Malaysia were selected based on pre-determined inclusion and exclusion criteria. A total number of 55 patients with 2 years post burn were invited. These patients volunteered and consented to participate in answering the psychometric battery containing Malay translated and validated questionnaires. The instruments that were used are, Malay PTSD Checklist for Civilians (MPCL-C), Beck Depression Inventory-Malay (BDI-Malay) and Burn Specific Health Scale- B . Results: Generally there are significant correlation of TBSA (burn severity) with post-traumatic stress disorder (PSTD), depression and quality of life (Qol). Development of PSTD and depression are found to be significant in patient with TBSA 15% and 14.7% respectively and quality of life is found to be significant in patient with TBSA 9% burn. Conclusion: Psychological evaluation should be a routine is postburn management. PTSD and depression are ~trong predictors in quality of life in post major burn. Therefore, treating burn patients holistically and beyond the visible scars, will lead to a better quality of life.